Clinical Observation of the Effectiveness of Fragrant Pandan Leaves (Pandanus Amaryllifolius Roxb.) To Lower Blood Pressure in Hypertensive Patients at Pratama Clinic Medan Tenggara - Muhammad Farhan Arifin; Yenita Yenita (UMSU, 2026)
Introduction: Nowadays, hypertension is a big problem. The disease is becoming more common. Alternative hypertension treatment includes many plant species. Fragrant pandan leaves are one example. Not many people know the antihypertensive properties of this herb. This study tested the effect of fragrant pandan leaf simplicia in lowering blood pressure in hypertensive patients. Methods: This study is an experimental study with pre-test and post-test without control group design. Twenty men and women were given 14 bags of pandan leaf simplicia in this study after which the study subjects drank 1 tea bag with 150-200ml of warm water twice a day for 7 days. Because systolic blood pressure data is normally distributed, a paired t-test is used, while diastolic blood pressure data is used a Wilcoxon test because the data is not normal. Results: Fragrant pandan leaves lowered blood pressure by 20/10 mmHg (p0.05). Discussion: Fragrant pandan leaves are effective in lowering blood pressure.